Data Descriptor: Smart Subsidies for Catchment Conservation in Malawi - Bell, Andrew R.; Ward, Patrick S.; Mapemba, Lawrence; Nyirenda, Zephania; Msukwa, Wupe; Kenamu, Edwin (International Food Policy Research Institute, 2018)
Conservation agriculture (CA) is a suite of land management practices aimed at improving soil structure, with a host of benefits for both the producer and the agricultural landscape. Manifesting itself in slightly different ways across the globe1, CA typically includes (i) no or minimal tillage of soils, (ii) retention and mulching of crop residues, and (iii) intercropping or rotation with other crops, usually legumes2. Under consistent and sustained adoption of CA practices for a period of several years, soils benefit from increased water retention and improved organic matter, with potential boosts to production for the farmer. At the same time, reduced runoff and soil erosion can provide benefits to water regulation and quality elsewhere in the agricultural landscape3. For Malawi, these cross-scale benefits are particularly important. Malawi’s largely rural economy is heavily invested in subsidized production of monoculture maize4 as a means of reducing reliance on food aid or imports2, with conventional tillage increasingly resulting in soil erosion with each new season’s rains. In the Shire River Basin, this enhanced sediment loading in riverine systems damages aquatic habitats, threatens farmers’ livelihoods, and dissipates the hydropower potential of dams that provide more than 90 percent of Malawi’s electricity5. CA has been widely promoted throughout Sub-Saharan Africa, but results have been largely disappointing. In particular, adoption rates are frequently as low as only a few percent of total cropped area across the region1,6, compared with nearly half of agricultural land under CA in the Americas1. Adoption studies have identified many private costs and risks that farmers must bear before benefits of CA might be realized—for example, years of increased weeding, lack of residues for livestock fodder, etc.—as discouraging experimentation, let alone sustained adoption7,8. Governmental and nongovernmental agencies interested in promoting CA often resort to providing incentives to farmers to encourage farmers to adopt CA. Yet it is rarely known a priori what magnitude of an incentive would be sufficient to overcome the private costs farmers initially bear, and there is often a great deal of heterogeneity in this regard that may make such approaches highly inefficient. Furthermore, despite years of CA adoption research, there are few universal predictors of CA adoption for Sub-Saharan Africa9, highlighting the importance of context and of a deeper look into the decision structure of adoption. The project from which the current datasets originate involved a two-year evaluation of a particular incentive, with two goals in mind. First, we aimed to undertake the first field evaluation of an “agglomeration payment”10,11, an innovative two-part incentive designed to encourage spatial coordination in adoption of conservation practices. It consists of a conventional subsidy (in the form of a voucher that could be used to purchase agricultural inputs through a local input dealer network) in exchange for participation, along with bonus payments for any neighboring farmers who also participate. This creates a range of potential network externalities—heterogeneous pricing as well as the potential for enhanced diffusion, encouragement, and self-policing of compliance—whose impact on CA adoption we wished to evaluate. Second, we wished to use our successive rounds of data collection to examine different aspects of farmer decisionmaking and preferences in order to better elucidate the structure of the adoption decision, both in the presence and absence of specific programs of encouragement, and to better identify contextual factors that encouraged or deterred adoption. This dataset includes a baseline and endline survey from a cluster-randomized sample of households within villages covering the five uppermost Extension Planning Areas (EPAs) in the Shire River Basin in southern Malawi, spanning the districts of Balaka, Machinga, and Zomba. These EPAs were identified by the Malawian Department of Land Resources Conservation (DLRC) as the key riparian areas to the Shire River . Additionally, it includes registration and monitoring data from two years of the experimental intervention, with the intervention consisting of varying incentive structures and visual monitoring of land management practices. Finally, the data include an accounting of what, if anything, recipients purchased with the voucher they received. In sum, these data include detailed assessments of farm and household characteristics; detailed crop-level measurements of inputs and production for all plots (baseline and endline surveys) or the main plot (intervention registrations; summaries at plot-level for all other plots); assessments of access to services, coupons, and markets; an economic experiment designed to assess marginal willingness-to-accept a CA incentive (baseline), and the perceived risks associated with CA (year 2 intervention and endline).